2019 environment, epigenetics and reproduction. Issue 4 (23rd December 2019) - Skinner, Michael K
Abstract: A conference summary of the fourth 2018 biannual Kenya Africa Conference 'Environment, Epigenetics and Reproduction' is provided. A special Environmental Epigenetics issue containing a number of papers in Volume 5, Issue 3 and 4 are discussed.